Pengenalan Bercocok Tanam Hidroponik Sederhana System Sumbu (Wick System) bagi Anak Usia SD Kelas 4-6 - Fransiska Mardiyana; Chanindra Dhimas; Arif Ramadhan; Riris Dwi Puspita; Zuniar Amanza Pratama Putra; Sumarmi Sumarmi (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
Agricultural development and farming methods are increasingly varied now. This development needs to be introduced as an agricultural innovation. Recognition to agriculture can be done through education. The agricultural innovation that will be introduced is the hydroponic wick system. This simple hydroponic system can be done by everyone. The activity was carried out at SD N 04 Wonorejo and was attended by grade 4-6 students. The method used is exposure, practice and question and answer. Students are given the task of growing and caring for spinach, red spinach and kale using a hydroponic wick system. Through question and answer, the students' interest and enthusiasm in agriculture can be seen.